Development and production of physiologically active biopreparations based on essential oil plants of Kyrgyzstan (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This paper presents essential oil plants with excellent insectoacaricidal properties. These plants synthesize valuable natural compounds in their organs and possess antimicrobial, anthelmintic, fungicidal, and other properties. The aim is to obtain affordable, therapeutic and prophylactic preparations from essential oil plants of the local flora for agricultural and veterinary needs, such as Cossack juniper, Tien Shan spruce, harmala, ferula, mountain ephedra, wormwood, common yarrow, and others. Complex recipes, doses, extracts, flours, granules, and a process flow chart have been developed.
Keywords: essential oil plants, therapeutic and prophylactic, fungicidal, insectoacaricidal, anthelmintic, doses, flours, granules